Promoting Healthy Aging: Physical Activity and Its Dual Effects on Physical Health and Cognitive Function in Chinese Older Adults - Li, Xing; Li, Chen (Frontiers in Public Health, 2025)
BackgroundWith the acceleration of societal aging, the physical health and cognitive function issues of seniors have increasingly garnered widespread attention. This article explores the impact of physical activity on the physical health and cognitive performance of seniors, aiming to provide a theoretical basis for health management and related policy formulation for seniors, which holds significant academic value and social significance.MethodsThis study constructs an ordered logit regression model to analyze the effects of physical activity on the physical health and cognitive performance of seniors, serving as the baseline model, and conducts a parallelism test to verify the model’s applicability. To ensure the robustness of the results, various methods were employed for testing, including model substitution, replacement of independent and dependent variables, and the use of propensity score matching analysis. Through these methods, the marginal effects of physical activity on the physical health and cognitive performance of seniors were revealed, and further analysis was conducted on the heterogeneity of physical health and cognitive performance among different groups and regions of seniors.Results(1) Physical activity has a significant promoting effect on the physical health and cognitive performance of seniors. Seniors who engage in physical activity demonstrate markedly better physical health and cognitive abilities compared to those who do not participate in physical activity, indicating that physical activity has a positive effect on improving the physical health and cognitive performance of seniors. (2) Physical activity exhibits notable marginal effects on the physical health and cognitive performance of seniors. The probability of seniors who participate in physical activity experiencing improvements in physical health and cognitive performance significantly increases, while those who do not engage in physical activity show the opposite trend, with a decrease in the probability of improvement. (3) There is significant heterogeneity in the effects of physical activity on the physical health and cognitive performance of different senior groups. Specifically, seniors who are female, married, or living in urban areas exhibit more pronounced improvements in health and cognition after engaging in physical activity, indicating that the benefits of physical activity are particularly prominent in these groups.DiscussionSeniors who participate in physical activity demonstrate significantly better physical health and cognitive abilities compared to those who do not engage in physical activity, suggesting that physical activity not only helps to delay physical aging but also effectively slows cognitive decline. Future policies should focus on enhancing the promotion and implementation of physical activity among seniors, especially within groups with differentiated needs, to advance the process of healthy aging and further enhance the overall well-being of the senior population.